1995
DOI: 10.1002/yea.320110404
|View full text |Cite
|
Sign up to set email alerts
|

Transient responses of Candida utilis to oxygen limitation: Regulation of the Kluyver effect for maltose

Abstract: The facultatively fermentative yeast Candida utilis exhibits the Kluyver effect for maltose: this disaccharide is respired and assimilated but, in contrast to glucose, it cannot be fermented. To study the mechanism of the Kluyver effect, metabolic responses of C. utilis to a transition from aerobic, sugar-limited growth to oxygen-limited conditions were studied in chemostat cultures. Unexpectedly, the initial response of maltose-grown cultures to oxygen limitation was very similar to that of glucose-grown cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Limited and slower rates of PDC production were observed with non-fermentable carbon sources such as maltose, citrate, acetate, and ethanol (Franzblau and Sinclair, 1983;Kaliterna et al, 1995;Weusthuis et al, 1994). Other authors have reported the induction of PDC in S. cerevisiae (Pronk et al, 1996;Sims and Barnett, 1991;Smits et al, 2000;van Dijken et al, 1993;van Hoek et al, 2000;Weusthuis et al, 1994), Kluyveromyces lactis (Destruelle et al, 1999;Zeeman et al, 2000), Rhizopus javanicus (Rosche et al, 2002a), and Zymomonas mobilis (Toh and Doelle, 1997) by manipulation of carbon source or dissolved oxygen.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Limited and slower rates of PDC production were observed with non-fermentable carbon sources such as maltose, citrate, acetate, and ethanol (Franzblau and Sinclair, 1983;Kaliterna et al, 1995;Weusthuis et al, 1994). Other authors have reported the induction of PDC in S. cerevisiae (Pronk et al, 1996;Sims and Barnett, 1991;Smits et al, 2000;van Dijken et al, 1993;van Hoek et al, 2000;Weusthuis et al, 1994), Kluyveromyces lactis (Destruelle et al, 1999;Zeeman et al, 2000), Rhizopus javanicus (Rosche et al, 2002a), and Zymomonas mobilis (Toh and Doelle, 1997) by manipulation of carbon source or dissolved oxygen.…”
Section: Introductionmentioning
confidence: 91%
“…Enhancement of PDC production in C. utilis has been extensively studied with increased induction under oxygen limited conditions in the presence of glucose (Franzblau and Sinclair, 1983;Kaliterna et al, 1995;Rogers, 1995, 1996;Weusthuis et al, 1994). Limited and slower rates of PDC production were observed with non-fermentable carbon sources such as maltose, citrate, acetate, and ethanol (Franzblau and Sinclair, 1983;Kaliterna et al, 1995;Weusthuis et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…The present study suggests that the fermentation capacity on lactose may be increased by specifically amplifying the LAC12 gene. The wellknown Kluyver effect for maltose utilization in Candida utilis (22,43) might also involve a limited maltose transport activity of this yeast.…”
Section: Vol 184 2002 Sugar Transporters In Fermentative Growth Of mentioning
confidence: 99%
“…Cloning of PDC genes in C. utilis While enhancement of the production of pyruvate decarboxylase in C. utilis has been well studied in terms of culture conditions, e.g., oxygen supplied and medium pH, [35][36][37][38] the PDC genes of C. utilis (CuPDC) have not previously been identified. In the present study, we cloned a CuPDC gene.…”
Section: Resultsmentioning
confidence: 99%